Identification and Management of COVID-19 Related Child and Adolescent Mental Health Problems: A Multi-Tier Intervention Model - Dhonju, Gunjan; Kunwar, Arun Raj; Karki, Utkarsh; Devkota, Narmada; Bista, Isha; Sah, Rampukar (Frontiers in Public Health, 2021)
Nepal is a low and medium-income country (LMIC), situated in South-east Asia, with a population of 29 million, of which, 40–50% are children and adolescents. The Coronavirus Disease 2019 (COVID-19) pandemic has affected the lives of people around the world, including Nepal. The child and adolescent mental health (CAMH) needs and services in Nepal have a significant gap. CAMH in Nepal suffers from lack of specialized training in this field as well as scarcity of human resources and services. There is only one full-time child and adolescent psychiatry (CAP) out-patient clinic in the country. Some recent activities have focused on CAMH in Nepal but the COVID-19 pandemic has produced new challenges. Access to mental health services for children and adolescents (C&A) across Nepal has been adversely affected. Factors such as closure of schools, confinement at home, lockdown, transportation problems, uncertainty, loss of usual routine and fear of infection have affected the mental health of C&A. This has highlighted a need to build capacity of available local human resources, enhance community support, teach measures of coping with stress and improve CAMH service delivery by strengthening the referral system, but these have to be addressed overcoming problems of travel restrictions and limited resources. To address these needs, online platform can be a suitable approach. With this view, a multi-tier CAMH intervention model was developed, which utilizes online platform for training mental health professionals across Nepal, who would then facilitate sessions for C&A, teachers, parents and caregivers; and link them to CAMH services locally, and remotely through teleconsultation. This started as a pilot from June 2020 and will continue till end of February 2021, with the aim to reach 40,000 C&A, parents, teachers and caregivers. As of Nov 2020, this model has been used to successfully conduct 1,415 sessions, with 28,597 population reached. Among them, 16,571 are C&A and 12,026 are parents, teachers and caregivers, across all 7 provinces of Nepal. In this paper, the multi-tier intervention to address the COVID-19 related CAMH problems has been discussed as a feasible framework for resource limited settings and LMICs like Nepal.